Partisipasi Masyarakat Lokal dalam Pengelolaan Daya Tarik Wisata Penangkaran Penyu Bali Fantasi Benoa - Firmansyah, Julian; Adikampana, I Made (JURNAL DESTINASI PARIWISATA; Vol 9 No 2 (2021): VOL 9, NO 2 (2021): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2021.v09.i02.p22, 2021)
Bali Fantasi is one of the turtle parks in Tanjung Benoa Village. Bali Fantasi turtle park is managed by local organization community. According to it, this research is to find out how that local communities managing Bali Fantasi to Parks Tourist Attraction. The research methodology used in this study is descriptive qualitative research, with observation, interview, literature study and documentation techniques. Data sources are obtained from primary data and secondary data. The theory or concept used is A4 concept (Attractions, Amenities, Access, Ancillary) and community participation theory. The result of this research represents the stage of local communities in managing Fantasi Turtle to Parks Tourist Attraction will be classified into induced participation. Local organization who managing Fantasi Turle Parks is under controlled by Badan Konservasi Sumber Daya Alam (BKSDA), local communities receive the income from tourist contributions and self – controlling Bali Fantasi Turle Parks Tourist Attraction which is done by local communities for security. Keyword: Turtle, Local Community Participation, Management